The Challenges of the Plain and Unambiguous Legal Interpretation of some of the Provisions of Nigeria Stamp Duties Act - Massajuwa, Florence Ulunma; Aidonojie, Paul Atagamen (NIU Journal of Social Sciences; Vol 6 No 3 (2020): KIU Journal of Social Sciences, Vol. 6 No. 3, September 2020DO - 10.58709/kiujss.v6i3.970.91-100, 2020)
Payment of taxes in Nigeria is a function of law, in other words, all taxes collected by Nigeria government are regulated by tax laws. It had been held in plethora of cases in Nigeria, that lawyers and judges are the custodian of the laws. They owed the general public the duty of interpreting and applying laws in its plain and ordinary meaning, and for the common good of humanity. However, it has been observed that there had been divergent interpretation of some provision of the Nigeria Stamp Duty Act, which in effect altered the intendment of the law. In view of the above, this research adopted qualitative methodology, using doctrinal method of research. It was therefore, concluded that an appropriate interpretation and application of the Nigeria Stamp Duty Act is an essential prerequisite in arriving at a just and logical decision, in ensuring justice is achieve for the common good of the general public. It was hereby recommended that, for there to be an appropriate interpretation and application of the Nigeria Stamp Duty Act, the custodian of the Nigeria laws must interpret the Stamp Duty Act in its plain and ordinary meaning as intended by the drafter. Keywords: Stamp Duties, Nigeria Stamp Duty Act, Stamp, Taxes, Tax laws, Stamp Document, Unstamped Document.